2011
DOI: 10.1111/j.1440-1754.2011.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Does after‐hours in‐house senior physician cover improve standard of care and outcomes in high‐risk preterm neonates? A retrospective cohort study

Abstract: Adoption of an ISPCR was not associated with any significant change in the standard of acute care and short-term outcomes for inborn neonates <32 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The other morbidities including PDA, IVH (grade ≥3) and BPD were not significantly different between the two groups. This finding is similar to other studies where significant differences in neonatal outcomes were not found after requiring a senior neonatologist or neonatal fellow to be in the NICU until 23:00 (19,20).…”
Section: Discussionsupporting
confidence: 91%
“…The other morbidities including PDA, IVH (grade ≥3) and BPD were not significantly different between the two groups. This finding is similar to other studies where significant differences in neonatal outcomes were not found after requiring a senior neonatologist or neonatal fellow to be in the NICU until 23:00 (19,20).…”
Section: Discussionsupporting
confidence: 91%
“…Resnick and colleagues retrospectively studied 480 infants born at less than 32 weeks of gestational age before and after adopting an after-hours in-house senior physician cover and reported no major differences in neonatal outcomes [7]. Lodha and colleagues retrospectively studied 387 preterm infants before and after the introduction of a 24 h in-house staff neonatologist cover and reported no significant difference in neurodevelopmental outcomes at three years corrected age [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although, these recommendations have been in place for a number of years and in the recent years some units in the United Kingdom have introduced resident consultant cover, the effect of this intervention on neonatal outcomes has not been evaluated in the UK [6]. Studies from Australia [7] and Canada [8] have reported no significant differences in neonatal or neurodevelopment outcomes at three years of age, but the studies were relatively small and their results might not be directly applicable to a different health system.…”
Section: Introductionmentioning
confidence: 99%
“…Lodha et al [18] concluded that there was no significant difference in neurodevelopmental outcomes at 3 years corrected age following 24 h a day in-house coverage by a staff neonatologist; however, it was associated with a reduction in the duration of mechanical ventilation in extremely preterm neonates. Resnick et al [19] reported that an after-hours in-house consultant neonatologist or neonatal fellow in the NICU until 11 p.m. showed no difference in outcomes of neonates < 32 weeks' gestation. We identified variations in the availability of in-house neonatologists, fellows, and residents 24 h a day/7 days a week, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%